Influence of chemical reactions and mechanism of peristalsis for the thermal distribution obeying slip constraints: Applications to conductive transportation - Naveed Imran; Asifa Tassaddiq; Maryiam Javed; Nasser Aedh Alreshidi; Muhammad Sohail; Ilyas Khan (Journal of Materials Research and Technology, 2020)
In this exploration, transportation of heat along with homogeneous–heterogeneous reactions for the peristaltic transport phenomenon by considering Ellis fluid model is reported in a symmetric channel comprising compliant walls. Using low Reynolds number and long wavelength assumptions, the governing system of equations of fluid transport problem is abridged and solved using the perturbation technique. The skin friction coefficient and Nusselt number are also incorporated in this contemplation. Particular attention is given to elastic parameters and Brinkman number and plotted their graphs for temperature, concentration, and velocity distribution. Results are deliberated in detail for the various non-Newtonian and Newtonian models. It is initiated that velocity distribution is enhanced for higher values of elastic parameters, which is because less resistance occurs at the channel walls. Relatively reverse comportment is portrayed in the case of concentration profile. The impact of heterogeneous and homogeneous reactions shows reverse bearing on the concentration field. It is comprehended that Brinkman number is an increasing function of viscous dissipation effects, which contribute to enhancing the temperature field for Newtonian and non-Newtonian cases. Moreover, augmentation in skin friction is noticed by escalating the parametric values of damping and rigidity. It is worth mentioning that, fluid velocity grows fastly for the Newtonian model case as compared with the non-Newtonian case by mounting the values of the elastic parameter. Moreover, the temperature field upsurges fastly in a non-Newtonian case as compared with the Newtonian case. The current investigation has an extensive range of use in biomedical science i.e. electromagnetic peristaltic micropumps.